The Social and Cultural Aspects of Waste Disposal Management in the Planning Revitalization of Riverbank Settlement - Oktarini, Maya Fitri; Hapsari, Harrini; Triyuli, Wienty (Bina Nusantara University, 2023)
The research discussed a strategy for revitalizing the slum settlement environment by previously mapping the geographical condition, the culture of living on the waterfront, as well as waste management practices by residents along the banks of the Musi River, Palembang. Most riverbank slums in the big city occupied dirty neighborhoods filled with garbage and waste. Most of the revitalization programs for riverbank waste management in Indonesia only focused on improving the physical quality with less attention to understanding the social and cultural aspects. These improvements resulted in temporary progress that relied on external interventions and subsidies. The interventions often resulted in temporary improvements because of the unsustainable approach. The field surveys collected data observations and interviews from homeowners within a radius of 100m from the riverbanks in four settlements with different physical environmental conditions. The survey collected data on communities’ use of river water for daily use and coping with flood conditions. The researchers processed all data to get a complete picture of the residents’ cultural view of living, potential, and constraints on waste disposal management. These results reveal the misunderstanding that residents in the settlements have no awareness of environmental cleanliness. On the contrary, they have the intention of mutual cooperation for environmental management. It is a potential strength in social ties and dependence on the community for developing sustainable environmental management strategies based on community empowerment. Improvements, both physical and infrastructure, should strengthen social bonds and community involvement in environmental management. Support in the waste disposal and management should aim to increase community cooperation in managing and monitoring the environment independently, not only at increasing awareness of cleanliness and health as always.